Peran Potensial Anemia Ibu dan Pemberian MP-ASI Terhadap Stunting di Wilayah Kerja Puskesmas Tamangapa Makassar - Nurlina Akbar; Andi Tenri Abeng (FORIKES, 2023)
The incidence of stunting is not only caused by nutritional factors but also environmental factors, the behavior of giving exclusive breastfeeding and complementary foods for breast milk, the mother's history of anemia, whether or not basic immunizations for toddlers are complete and ownership of MCH books. The aim of this research was to determine the determinants of stunting in toddlers in the Tamangapa Community Health Center area as a final waste disposal site in Makassar City. This research implemented a case control design, involving 27 stunted toddlers and 27 non-stunting toddlers, who were selected using a purposive sampling technique. Data was collected through interviews and filling out questionnaires. Then analysis was carried out using the Chi-square test. The results of the study showed that factors related to the incidence of stunting were maternal anemia (p = 0.000; OR = 12.6) and giving complementary foods for breast milk (p = 0.023; OR = 0.21). Meanwhile, factors that were not related to the incidence of stunting were exclusive breastfeeding (p = 0.398; OR = 1.90), immunization history (p = 0.326; OR = 2.42), source of drinking water (p = 0.224; OR = 0.38 ) and ownership of MCH books (p = 1,000; OR = 0.74). This research proves that maternal anemia and the provision of complementary foods for breast milk are determinants of the incidence of stunting in toddlers in the Tamangapa area.Keywords: stunting; determinant; maternal anemia; complementary foods for breast milk ABSTRAK Kejadian stunting tidak hanya disebabkan oleh factor gizi namun juga faktor lingkungan, perilaku pemberian ASI eksklusif dan makanan pendamping ASI, riwayat anemia ibu, lengkap tidaknya imunisasi dasar balita serta kepemilikan buku KIA. Tujuan penelitian ini adalah mengetahui determinan kejadian stunting pada balita di wilayah Puskesmas Tamangapa sebagai tempat pembuangan akhir sampah Kota Makassar. Penelitian ini menerapkan desain case control, yang melibatkan 27 balita stunting dan 27 balita tidak stunting, yang dipilih dengan teknik purposive sampling. Data dikumpulkan melalui wawancara dan pengisian kuisioner. Lalu dilakukan analisis dengan uji Chi-square. Hasil penelitian menunjukkan bahwa faktor yang berhubungan dengan kejadian stunting adalah anemia pada ibu (p = 0,000; OR = 12,6) dan pemberian makanan pendamping ASI (p = 0,023; OR = 0,21). Sedangkan faktor yang tidak berhubungan dengan kejadian stunting adalah ASI eksklusif (p = 0,398; OR = 1,90), riwayat imunisasi (p = 0,326; OR = 2,42), sumber air minum (p = 0,224; OR = 0,38) dan kepemilikan buku KIA (p = 1.000; OR = 0,74). Penelitian ini membuktikan bahwa kondisi anemia ibu dan pemberian makanan pendamping ASI merupakan determinan bagi kejadian stunting pada balita di wilayah Tamangapa.Kata kunci: stunting; determinan; anemia ibu; makanan pendamping ASI